The Aesthetics of Development : Art, Culture and Social Transformation - Clammer, John; Giri, Ananta Kumar (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
Through a unique range of theoretical and practical case studies, this collection considers the relationship between the arts (understood as the visual arts, crafts, theatre, dance, and literature) and development, creating both a bridge between them that is rarely explored and filling in concrete ways the content of the "culture" part of the equation "culture and development". It includes manifestations of culture and the ways in which they relate to development, and in turn contribute to such pressing issues as poverty alleviation, concern for the environment, health, empowerment, and identity formation. It shows how the arts are an essential part of the concrete understanding of culture, and as such a significant part of development thinking - including the development of culture, and not only of culture as an instrumental means to promote other development goals.